Case report Diffuse cutaneous mastocytosis with anaphylaxis - Lange, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Diffuse cutaneous mastocytosis (DCM) is a very rare form of cutaneous mastocytosis occurring almost exclusively in infants. In DCM there is widespread cutaneous mast cell (MC) proliferation involving the entire or almost the entire skin. Diffuse thickening of the skin, yellowish-orange pigmentation, pronounced Darier’s sign and tendency towards extensive bullous eruptions are characteristic changes of this disorder. Degranulation of MC results in development of mediator-related symptoms: hypotension, bronchospasm, diarrhoea, vomiting, flushing and gastrointestinal bleeding. The risk of internal organ involvement is difficult to estimate because DCM is uncommon; however, mast cell infiltration of bone marrow and the reticuloendothelial system has been reported. We present a 3-year-old boy suffering from DCM with generalized bullous rash, severe mediator-related symptoms and anaphylaxis.